Survey Fatigue During the COVID-19 Pandemic: An Analysis of Neurosurgery Survey Response Rates - de Koning, Rosaline; Egiz, Abdullah; Kotecha, Jay; Ciuculete, Ana Catinca; Ooi, Setthasorn Zhi Yang; Bankole, Nourou Dine Adeniran; Erhabor, Joshua; Higginbotham, George; Khan, Mehdi; Dalle, David Ulrich; Sichimba, Dawin; Bandyopadhyay, Soham; et al. (Frontiers in Surgery, 2021)
Background: The COVID-19 pandemic has caused a surge in research activity while restricting data collection methods, leading to a rise in survey-based studies. Anecdotal evidence suggests this increase in neurosurgical survey dissemination has led to a phenomenon of survey fatigue, characterized by decreased response rates and reducing the quality of data. This paper aims to analyze the effect of COVID-19 on neurosurgery surveys and their response rates, and suggest strategies for improving survey data collection. Methods: A search was conducted on March 20, 2021, on Medline and EMBASE. This included the terms “neurosurgery”, “cranial surgery”, “spine surgery”, and “survey” and identified surveys written in English, on a neurosurgical topic, distributed to neurosurgeons, trainees, and medical students. Results were screened by two authors according to these inclusion criteria, and included articles were used for data extraction, univariable, and bivariable analysis with Fisher’s exact test, Wilcoxon rank-sum test, and Spearman’s correlation. Results: We included 255 articles in our analysis, 32.3% of which were published during the COVID-19 pandemic. Surveys had an average of 25.6 (95% CI=22.5-28.8) questions and were mostly multiple choice (78.8%). They were disseminated primarily by email (75.3%, 95% CI=70.0-80.6%) and there was a significant increase in dissemination via social media during the pandemic (OR=3.50, 95% CI=1.30-12.0). COVID-19 surveys were distributed to more geographical regions than pre-pandemic surveys (2.1 vs. 1.5, P=0.01) and had higher total responses (247.0 vs. 206.4, P=0.01), but lower response rates (34.5% vs. 51.0%, P<0.001) than pre-COVID-19 surveys. Conclusion: The rise in neurosurgical survey distribution during the COVID-19 pandemic has led to survey fatigue, reduced response rates, and data collection quality. We advocate for population targeting to avoid over-researching, collaboration between research teams to minimize duplicate surveys, and communication with respondents to convey study importance, and we suggest further strategies to improve response rates in neurosurgery survey data collection.